Awareness of surgical expenditure amongst UK trainees and consultants: A questionnaire study. (July 2019) - Povey, M.; Francis, N.; Healy, R.; Blacker, S.; Vimalachandran, D.; Sutton, P.A.
Abstract: Introduction: Limited knowledge of surgical device and service costs restricts a surgeon's ability to make cost efficient choices and contribute to the efficiency savings required by the NHS to reduce the financial deficit. This study aims to assess how aware surgeons are of surgical equipment and regularly used services. Methods: A single sided hard copy questionnaire asking for the estimate cost of 24 surgical devices/services was handed out to individuals at two separate UK annual conferences. Items and services which are regularly used and/or clinically significant were selected and, where possible, alternatives to those items were included for comparison. Participants were also asked for their grade and specialty. An estimate was deemed correct if it was within 20% of the actual cost. Planned subgroup analyses for grade and specialty were performed. Results: The 143 participants consisted of 23 (16%) consultants, 39 (27%) registrars, 33 (23%) SHOs and 48 (34%) foundation doctors. Of the 95 participants who were SHO grade or more senior, 67 (71%) work within general surgery. Across all items, only 9.6% of estimates were correct. There was no statistically significant difference between training levels (consultant 11.5%, registrar 10.1%, SHO 8.6%, foundation 8.9%; p = 0.253). Participants were significantly less successful in correctly estimating the cost of high value (>£150 [USD 198; EUR €175]) items (8.5% vs. 11.1%); p = 0.011, and the cost of devices as compared to the cost of services (7.4% vs. 15.0%); p = 0.001. Conclusion: Surgeons across all grades and specialties have poor knowledge of device and service costs. It is important that this improves in order to allow surgeons to make a meaningful contribution to NHS efficiency savings by making informed decisions about their use of devices and services. Highlights: Surgeons across all grades and specialties have poor knowledge of device and service costs. There was no statistically significant difference between training levels. No statistically significant difference between general surgery and non-general surgery participants. Participants were significantly less successful in correctly estimating the cost of high value (>£150) items. Participants significantly less successful in correctly estimating cost of devices as compared to the cost of services.